Noninvasive assessment of myocardial bridging by coronary flow velocity reserve with transthoracic Doppler echocardiography: vasodilator vs. inotropic stimulation. (15th December 2016) - Aleksandric, Srdjan; Djordjevic-Dikic, Ana; Beleslin, Branko; Parapid, Biljana; Teofilovski-Parapid, Gordana; Stepanovic, Jelena; Simic, Dragan; Nedeljkovic, Ivana; Petrovic, Milan; Dobric, Milan; Tomasevic, Miloje; Banovic, Marko; et al.
Abstract: Background: To consider hemodynamic assessment of myocardial bridging (MB) adequate, it is believed that inotropic stimulation with dobutamine should be estimated because its dynamic nature depends on the degree of extravascular coronary compression. This study evaluated comparative assessment of hemodynamic relevance of MB using coronary flow velocity reserve (CFVR) measurements by transthoracic Doppler echocardiography (TTDE) with vasodilatative and inotropic challenges. Methods: This prospective study included forty-four patients with angiographic evidence of isolated MB of the left anterior descending coronary artery (LAD) and systolic compression of ≥ 50% diameter stenosis. All patients were evaluated by exercise stress-echocardiography (ExSE) test for signs of myocardial ischemia, and CFVR of the distal segment of LAD during iv.infusion of adenosine (ADO:140 μg/kg/min) and iv.infusion of dobutamine (DOB:10-40 μg/kg/min), separately. Results: Exercise-SE was positive for myocardial ischemia in 8/44 (18%) of patients. CFVR during ADO was significantly higher than CFVR during peak DOB (2.85 ± 0.68 vs . 2.44 ± 0.48, p = 0.002). CFVR during peak DOB was significantly lower in SE-positive group in comparison to SE-negative group (2.01 ± 0.16 vs . 2.54 ± 0.47, p < 0.001), but not for ADO (2.47 ± 0.51 vs . 2.89 ± 0.70, p = 0.168), respectively. Multivariable logistic analysis showed that CFVR peak DOB was the most significant predictor of functional significant MB (OR 0.011, 95%CI: 0.001–0.507, p = 0.021). Receiver-operating characteristic curves have shown that TTDE-CFVR obtained by high-dose of dobutamine infusion is better than those by adenosine regarding to functional status of MB (AUC 0.861, p = 0.004; AUC 0.674, p = 0.179, respectively). Conclusions: Non-invasive CFVR measurement by TTDE during inotropic stimulation, in comparison to vasodilation, provides more reliable functional evaluation of MB. Highlights: Dobutamine dose > 20 μg/kg/min induced maximal hyperemia much like adenosine. Dobutamine-induced hyperemia is equivalent to adenosine-induced one only in patients with myocardial ischemia. CFVR during inotropic stimulation provides more reliable functional evaluation of MB. MB decompression is slow and incomplete, and reaches its maximum at mid-diastole. MB compression at mid-to-end-diastole is higher in patients with myocardial ischemia.